Elucidation of the role of guanidinium incorporation in single-crystalline MAPbI3 perovskite on ion migration and activation energy. Issue 20 (11th May 2020) - Mahapatra, Apurba; Runjhun, Rashmi; Nawrocki, Jan; Lewiński, Janusz; Kalam, Abul; Kumar, Pawan; Trivedi, Suverna; Tavakoli, Mohammad Mahdi; Prochowicz, Daniel; Yadav, Pankaj
Abstract : We have studied the effect of guanidinium incorporation in a single-crystalline MAPbI3 perovskite on ion migration using temperature-dependent electrochemical impedance spectroscopy. Abstract : Ion migration plays a significant role in the overall stability and power conversion efficiency of perovskite solar cells (PSCs). This process was found to be influenced by the compositional engineering of the A-site cation in the perovskite crystal structure. However, the effect of partial A-site cation substitution in a methylammonium lead iodide (MAPbI3 ) perovskite on the ion migration process and its activation energy is not fully understood. Here we study the effect of a guanidinium (GUA) cation on the ion transport dynamics in the single crystalline GUA x MA1− x PbI3 perovskite composition using temperature-dependent electrochemical impedance spectroscopy (EIS). We find that the small substitution of MA with GUA decreases the activation energy for iodide ion migration in comparison to pristine MAPbI3 . The presence of a large GUA cation in the 3D perovskite structure induces lattice enlargement, which perturbs the atomic interactions within the perovskite lattice. Consequently, the GUA x MA1− x PbI3 crystal exhibits a higher degree of hysteresis during current–voltage ( J – V ) measurements than the single-crystalline MAPbI3 counterpart. Our results provide the fundamental understanding of hysteresis, which is commonly observed in GUA-based PSCs and a general protocol for in-depth electrical characterization of perovskite single crystals.